Intra-Articular Umbilical Cord Derived Mesenchymal Stem Cell Therapy for Chronic Elbow Osteoarthritis in Dogs: A Double-Blinded, Placebo-Controlled Clinical Trial - Kim, Stanley E.; Pozzi, Antonio; Yeh, Jiunn-chern; Lopez-Velazquez, Mariana; Au Yong, Jo Anne; Townsend, Sarah; Dunlap, Anna E.; Christopher, Scott A.; Lewis, Daniel D.; Johnson, Matthew D.; Petrucci, Kathryn (Frontiers in Veterinary Science, 2019)
Background: Intra-articular stem cell therapy may help alleviate lameness caused by osteoarthritis in dogs. Umbilical cord-derived stem cell (UMSC) therapy has not yet been investigated in a veterinary clinical study. We hypothesized that dogs treated with intra-articular UMSC will have improved limb function and quality of life when compared to dogs treated with a saline placebo injection. Methods: This was a prospective, double-blinded, placebo-controlled clinical trial in client-owned dogs with chronic elbow osteoarthritis with a follow-up time of 6 months. Dogs were assigned to receive intra-articular UMSC (n=38) or a saline placebo intra-articular injection (n=30). Outcome measures included the Canine Brief Pain Inventory score (CBPI) and peak vertical force (PVF) from force-platform gait analysis. Treatment was considered successful when there was a decrease in the Pain Severity Score of at least 1 and a decrease in the Pain Interference Score of at least 1 from baseline. Success rates and PVF were compared between groups. Results: No adverse effects associated with UMSC were noted. Of the dogs completing the study, treatment success in the UMSC (n=28) vs placebo groups (n=23) was observed in 54% vs 28% of dogs at 1 month, 50% vs 27% at 3 months, and 46% vs 14% at 6 months, respectively. Success rate in the UMSC group was significantly higher than the placebo group at 1 month and 6 months after treatment. However, no differences in PVF of the affected limb over time was observed in either group. Conclusions: Intra-articular UMSC for osteoarthritis may improve clinical signs based on owner observations.